Substitutional Sodium Doping on Tungsten Ditelluride: A First-principles Study - Subedi, Bibek; Adhikari, Narayan (BIBECHANA, 2022)
Methylation at O6 atom of guanine is a type of DNA damage which can cause a cancer. This damage at O6 atom of guanine in a DNA can be transferred to SG atom of cysteine in O6-alkylguanine-DNA alkyltransferase (AGT). Flipping out of methylated guanine from its base stack is essential to give off the methyl adduct (CH3) to AGT. AGT receives the methyl adduct at cysteine leaving guanine demethylated, but still in flipped out orientation. The repair mechanism of DNA would be completed only when the extrahelically flipped guanine returns back into the base stack, which is considered as the final step of the DNA repair mechanism. Here, the intrahelical flipping mechanism of repaired guanine has been studied. The work is further extended to examine the stability of hydrogen bonds between guanine and its pair partner cytosine. The overall result shows that intrahelical rotation of repaired guanine is possible and the base pairing is stable as the ordinary hydrogen bonding. BIBECHANA 19(2022)184-194